Contingent Workforce as a Remedy to Overcome the Employee-Shortage Issues in Vodafone-Oman Company - Kawther Musabah Alghafri; Muadh Khalfan AlSiyabi; Bashaer Mabrook Albusaidi; Hafsa Mahmood Alhadi; Dr. Chandra Sekhara Reddy Kamireddy (International Journal of Engineering and Management Research, 2023)
Most of the companies in the recent days facing the issues of the shortage of the skilled workforce. Recruiting and the retaining the right kind and right type of personnel is a big challenge to the team of HR in the organizations. To overcome this shortage issues one of the strategy what the companies are following is contingent workforce. As per the recent studies it is observed that, the companies are gaining major advantages and minor drawbacks through contingent workforce. Contingent workforce is available in various forms like temporary workers, freelancers, casual earners and contractors. It is easy to hire and fire these employees as per the company workload requirements. Companies are preferring these contingent employees for more than one reason i.e: cost-saving benefit, seasonal fluctuations, no need to bother about extra incentives and training programs e.t.c. Vodafone-Oman is a couples of years old company started with the motto of to connect everybody in the country Oman for the sake of enhanced future and their solutions are aimed to impact the people positively. As a company with technology, it holds the Sultanate of Oman’s 2040 Vision and the goals about the Sustainable Development. It supports the Sultanate position at the head of creativity and innovation in both locally and globally. After the commencement of the company’s pilot operations on 30th December 2021, the Vodafone company commemorated its operations launch officially on 6th March, 2021 in the Sultanate of Oman. As a newly started company Vodafone-Oman is also facing an issues of skilled worker’s shortage. As a remedy to overcome this issue the company is started using contingent workforce to give the tough competition to its competitors and to reach the maximum number of customers at the earliest.